The Application of RCRR (Read, Cover, Remember, Retell) Technique in Teaching Reading at Junior High School - Ifna Nifriza; Sri Mures Walef (EDULIA: English Education, Linguistic and Art Journal, 2023)
This research was experimental research. The population of this research was the VIII grade students of SMPN 2 Kec. Luak Payakumbuh. There were four classes of the eight grade students, total population was 88 students. The sample of this research had chosen by using cluster sampling. The experimental class was VIII.3 that had taught by using Read, Cover, Remember, Retell (RCRR) strategy and the control class was VIII.4 had taught by using conventional class in teaching reading. The instrument of this research was reading test in multiple choice test form. It was valid because the students have learnt the material. Then, the instrument was reliable because the result of split-half was 0.65 gave positive association. To get the data, the researcher used the t-test formula that suggested by Gay and Airasian. The result of the research was analyzed by t-test formula and the researcher got t-calculated was 8.38. After that, the researcher compared to t-table was 2.021. Where the level of significant was 0.05 with degree of freedom was 43. After analyzing the data, the researcher got t-count higher than t-table. So, the null hypothesis (H0) was rejected and alternative hypothesis (H1) was accepted. It means there was a significant effect of teaching reading by using Read, Cover, Remember, Retell (RCRR) strategy at the eight grade students of SMPN 2 Kec. Luak. Keywords : RCRR, Teaching Reading, The Application.